Cryptocurrencies in The Function of the Regional Development Strategy of the Republic of Serbia - Dobrodolac Šeregelj, Tinde; Brdar, Jelena (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
New technologies in the financial market and innovation in the few past years created new type of asset, well known as Cryptocurrency. This virtual currency was very quickly accepted in financial world. Market of cryptocurrency have high price movement, volatility and strategy for forecasting is very complex and plays an important role in strategic management. Many researchers have begun to develop forecasting models and to explore portfolio optimization with cryptocurrency as a new investment asset, all in order to find the right strategy. In this paper we analyzed data from cryptocurrency exchange platform CoinMarketCap. The CoinCap API provides real time pricing and market activity for over 1000 cryptocurrencies. It collects exchange data from thousands of markets for transparent and accurate data on asset price. For our research we selected 15 cryptocurrencies (Bitcoin, Ethereum, XRP, DASH, Litecoin, Tether, EOS, Binance Coin, Bitcoin SV, Monero, Cardano, Stellar, IOTA, TRON and Huobi Token). Research has been developed in two directions. Objective in first part of this paper are to search for price volatility, correlation and relationship between selected cryptocurrencies. Since that price trend are with high oscillations many investors with high risk tolerance are interested to invest in Cryptocurrency. Because of that in the second part of research we create an investment portfolio based on Modern Theory approach, all in order to find the right strategy. The main goal of research paper is to explore risk diversification and to measure effectiveness of the portfolio with cryptocurrencies, which is a great help to experts in making business decisions and in choosing the right strategy for development.